Magnetic Resonance Imaging Biomarker of Axon Loss Reflects Cervical Spondylotic Myelopathy Severity. Issue 9 (May 2016) - Murphy, Rory K. J.; Sun, Peng; Xu, Junqian; Wang, Yong; Sullivan, Samir; Gamble, Paul; Wagner, Joanne; Wright, Neill N.; Dorward, Ian G.; Riew, Daniel; Santiago, Paul; Kelly, Michael P.; et al.
Abstract : Study Design: A prospective cohort study. Objective: In this study, we employed diffusion basis spectrum imaging (DBSI) to quantitatively assess axon/myelin injury, cellular inflammation, and axonal loss of cervical spondylotic myelopathy (CSM) spinal cords. Summary of Background Data: A major shortcoming in the management of CSM is the lack of an effective diagnostic approach to stratify treatments and to predict outcomes. No current clinical diagnostic imaging approach is capable of accurately reflecting underlying spinal cord pathologies. Methods: Seven patients with mild (mJOA ≥15), five patients with moderate (14≥mJOA ≥11), and two patients with severe (mJOA <11) CSM were prospectively enrolled. Given the low number of severe patients, moderate and severe patients were combined for comparison with seven age-matched controls and statistical analysis. We employed the newly developed DBSI to quantitatively measure axon and myelin injury, cellular inflammation, and axonal loss. Results: Median DBSI-inflammation volume is similar in control (266 μL) and mild CSM (171 μL) subjects, with a significant overlap of the middle 50% of observations (quartile 3 – quartile 1). This was in contrast to moderate CSM subjects that had higher DBSI-inflammation volumes (382 μL; P  = 0.033). DBSI-axon volume shows a strong correlation with clinical measures ( r  = 0.79 and 0.87, P  = 1.9 x 10–5 and 2 x 10–4 for mJOA and MDI, respectively). In addition to axon and myelin injury, our findings suggest that both inflammation and axon loss contribute to neurological impairment. Most strikingly, DBSI-derived axon volume declines as severity of impairment increases. Conclusion: DBSI-quantified axonal loss may be an imaging biomarker to predict functional recovery following decompression in CSM. Our results demonstrate an increase of about 60% in the odds of impairment relative to the control for each decrease of 100 μL in axon volume. Level of Evidence: 3